The Incidence of Complications of Dental Trauma and Associated Factors: A Retrospective Study - Ines Kallel; Nabiha Douki; Syrine Amaidi; Faten Ben Amor (International Journal of Dentistry)
Objective. The aim of this work was to study the incidence of complications of dental traumatisms and look for associations between factors related to trauma and the occurrence of complications. Materials and Methods. It is a longitudinal retrospective study on a sample of 125 traumatized teeth. The sample is taken from patients consulting the dentistry service at the hospital Sahloul Sousse between 2014 and 2017. Criteria for including a patient were presence of a permanent incisor affected by a subluxation, intrusion, lateral luxation, extrusion, or avulsion injuries associated or not with concomitant dentoalveolar injuries. Data were collected using a questionnaire. The information about etiology of trauma, delay of consultation, orientation of the patient, kind of injury, and emergency treatment and complications were obtained from the patients’ records. Results. The incidence of complications was 8%: external root resorption was present in 70% of cases, surface resorption was observed in 10% of cases, and replacement resorption in 10%, ankylosis in 10%. About pulpal complications, pulp necrosis was found after 4 weeks of follow-up, as well as the internal root resorption after one year. The most common cause of the trauma was the fall (40%). The majority of patients came for emergency consultation within “1 to 3 days,” and the coronary fracture without pulp exposure was the first diagnosis (20.60%). Statistical analysis showed no significant relationship between the cause of the trauma and the complication (P=0.577) and between the delay of consultation and complication (P=0.143). However, an association between consultation time and patient orientation was found (P=0.009). Conclusion. Treatment of dental injuries is usually delayed and not given as much attention as general medical treatment that can explain the occurrence of pulpal and periodontal complications. Immediate consultation and treatment could improve long-term prognosis of the injured tooth.